The Problem of Non-Execution of Decisions of the Constitutional Court of the Russian Federation - V. R. Borisova (Теоретическая и прикладная юриспруденция)
In the article the author analyzes the problem of non-execution of decisions of the Constitutional Court of the Russian Federation. It is emphasized that this circumstance undermines the supremacy of the Constitution of the Russian Federation. The author gives a specific example, when a decision of the Constitutional Court of the Russian Federation was issued in the interests of the applicants, however, the corresponding federal law was not adopted in the manner prescribed by law. Solutions to this problem are proposed. The necessity of allowing the courts of the Russian Federation to allow the possibility of appealing against the inaction of the State Duma of the Federal Assembly of the Russian Federation according to the rules of Chapter 22 of the Code of Administrative Procedure is substantiated. The author criticizes the position of the Supreme Court of the Russian Federation on the impossibility of such actions if the adoption or amendment of a federal law has become the subject of consideration by the Constitutional Court of the Russian Federation. It is concluded that such a position violates the constitutional principle of separation of powers.